Hebella plana Ritchie 1907 ... - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
Hebella plana Ritchie, 1907 (Fig. 9) Hebella plana— Totton, 1930: 156–157, fig. 12a, b; Peña Cantero et al., 2004: 2290–2291 (synonymy); Peña Cantero, 2008: 454; 2010b: 766; 2014a: 1718, fig. 2g, h. Hebella striata var. plana — Jäderholm 1926: 4. Material examined. Stn 53, several hydrothecae on Staurotheca densa, S. nonscripta, and Staurotheca sp. (MNCN 2.03/539); Stn 67, a few hydrothecae on S. nonscripta and Halecium exaggeratum Peña Cantero, Boero & Piraino, 2013 (NIWA 117499); Stn 108, two hydrothecae on Antarctoscyphus spiralis (Hickson & Gravely, 1907) (NIWA 117500); Stn 126, six hydrothecae on Staurotheca densa (MNCN 2.03/540); Stn 139, a few hydrothecae on Staurotheca nonscripta (NIWA 117501); Stn 140, several hydrothecae on Staurotheca nonscripta and S. dichotoma Allman, 1888 (NIWA 117502); Stn 148, a few hydrothecae on S. nonscripta (MNCN 2.03/541); Stn 178, a few hydrothecae on Staurotheca compressa Briggs, 1938 (NIWA 117503). Remarks. In the material from Stn 178 some hydrothecae seem to ... : Published as part of ÁLVARO L. PEÑA CANTERO, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa, pp. 1-65 in Zootaxa 4293 (1) on page 24, DOI: 10.11646/zootaxa.4293.1.1, http://zenodo.org/record/828475 ...